Volunteer Work Culture and the Formation of Social Capital Among Youth: A Field Study in Erbil City (Journal of the College of Education for Women, 2025)
The study tried to reveal the impact of youth participation in volunteer activities on the formation of social capital values to them. It relied on the descriptive approach and on more than one tool in collecting its data; (interview, observation, focus discussion), and the application of the study is in Erbil Governorate. The study relied on a sample of young volunteers; 49 young people participating in volunteer work, and 10 young volunteers from different social and institutional backgrounds to benefit from their opinions and experiences in enriching field study. The results of the study revealed that participation in volunteer work plays an important role in building trust among youth and among youth and society. When young people participate in volunteer activities, they learn how to collaborate with others and build positive relationships with them, which contributes to building trust between them and the community. Also, volunteering brings youth to new skills and enable them to make a positive impact in society. The study concluded that there is a positiv relationship between the values of social capital and the trend towards volunteering, as it shows that youth possess high values of social capital due to participating in volunteering. So, institutions can work to promote the values of social capital among young people by organizing awareness and educational programs aimed at enhancing trust, cooperation and social participation. This can contribute to increasing the participation of youth in volunteerism and enhancing their positive role in society.